What about 100% juice and non-sugar sweeteners? A national study of support for taxes, labelling and marketing bans applied to sugary drinks, non-sugar sweetened beverages and 100% juice in Australia - Caroline Miller; Kerry Ettridge; Enola Kay; Joanne Dono (Australian and New Zealand Journal of Public Health)
Objective: To assess levels of support for potential policy interventions (labelling, banning marketing to children, taxes) to reduce sugar-sweetened beverage consumption; and to assess levels of support when these policies were extended to non-sugar sweetened beverages and 100% fruit juice. Methods: Data, collected via a nationally representative online survey of Australian adults (N=2,876), measured support (5-point Likert scales; strongly/somewhat in favour/against, or neutral) for front-of-pack warning labels, banning marketing to children, and taxes, applied to the three beverages. Chi-square (unadjusted) and logistic regressions (adjusted) assessed support. Results: Support was highest for sugar-sweetened beverage policies, followed by non-sugar-sweetened beverages, and lowest for juice. Across all beverages, support was highest for labelling (83%, 82%, 71%, respectively), followed by marketing bans (73%, 60%, 25%), and taxes (56%, 39%, 14%). Support was typically lower among younger, less educated, most socioeconomically disadvantaged and regular consumers. Conclusions: Results indicate high receptiveness among the Australian community for beverage policies, especially warning labels, with lower receptiveness towards some policies targeting juice. Implications for Public Health: These findings can inform the development of effective public health strategies for encouraging healthier beverage consumption, and point to prioritising front-of-pack warning labels, given the consistently high support for this policy.